2016
DOI: 10.14429/djlit.36.1.8959
|View full text |Cite
|
Sign up to set email alerts
|

Use of E-resources by the Medical Students of M.M. University, Ambala: A Case Study

Abstract: This paper reports usage and experience of e-resources medical students at Maharishi Markandeshwar University, Ambala Haryana. In this study it is try to verify and evaluate the purpose, frequency, reasons of using and place of students access to e-resources. A well structured questionnaire was administered to the 100 medical students. The response rate was 78% (45 from Postgraduates and 33 from Undergraduates students). The result of study reveals that most of P.G. and U.G. students state that e-resources are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…This finding portrays positive perceptions towards use of e-resources by these academics. In addition, this finding concurs with studies that note that ease of use is significantly associated with the usage behaviour of the users 24 . Ease of use could increase the utilisation of the e-resources among the academics at UNIVEN.…”
Section: Ease Of Usesupporting
confidence: 91%
“…This finding portrays positive perceptions towards use of e-resources by these academics. In addition, this finding concurs with studies that note that ease of use is significantly associated with the usage behaviour of the users 24 . Ease of use could increase the utilisation of the e-resources among the academics at UNIVEN.…”
Section: Ease Of Usesupporting
confidence: 91%
“…This study has therefore found that postgraduate students prefer to access the internet from the library than from other locations. The studies of Chandran (2013), Mittal and Bala (2013) and Kumar (2016) also revealed that most of the students accessed the internet from the library. This study seems to concur with the findings by Twill (2012) that people from disadvantaged rural communities rely on libraries for internet access.…”
Section: Preferred Location Of Access To the Internet And Elrsmentioning
confidence: 99%
“…At this stage, they can use a variety of ways to collect user feedback such as conduct user surveys, study log files, number of downloads and registrations. This feedback is essential for the renewal of the database (Ashcoft and McIvor, 2001;Geller, 2006;Feather, 2007;Breeding, 2008;Kumar, 2016). In practice, librarians usually depend upon publishers' log files and do not vet that with any other method.…”
Section: Review Of Literaturementioning
confidence: 99%